Surgical Skills Workshops Should Be a Part of the United Kingdom Undergraduate Medical Curriculum - Hakim, Muhammad A (Cureus, 2019)
Introduction: Medical students across the United Kingdom (UK) report poor satisfaction with surgical teaching. The Surgical Skills Day (SSD) begins to address this by exposing medical students to surgery through an easily accessible one-day practical workshop. This study shows how the SSD encourages undergraduate engagement in surgery. Method: Feedback forms were emailed to attendees of the SSD and their anonymised responses were used to evaluate the SSD. Results: A total of 144 students attended the SSD across three years and the feedback response rate was 74% (n = 107). Key findings were that 100% of respondents (n = 107) would like the SSD to be an annual event, 79% (n = 83) were more inclined to pursue a surgical career following the event, and 97% (n = 103) would like to see practical surgical skills incorporated into the curriculum. The SSD was able to engage undergraduates with surgery through mentorship, practical skills, specialty exposure, and teaching of the General Medical Council (GMC) mandated skills. Conclusions: Undergraduate surgical teaching in the UK is insufficient. The student-led annual SSD showed improved engagement in practical surgical skills and increased enthusiasm for a surgical career. In light of this, the authors feel the SSD or similar event should be integrated into the UK medical school curriculum.